Karakteristik Mekanik Papan Partikel Komposit Serbuk Kayu Jati Matriks Resin Polyester dengan Variasi Fraksi Massa - Kariana, I Nengah; Kencanawati, C.I.P.K; Putra Negara, D.N.K (Teknik Desain Mekanika; Vol 10 No 2 (2021): April 2021 : Teknik Desain Mekanika, 2021)
Abstract The community's need for wood is increasingly difficult to fulfill because the potential and availability of felling in natural forests is decreasing. The type of waste generated from the woodworking industry is sawn timber waste. Waste of teak sawn in the form of powder can be reused so that it has an added value, namely by combining it with polyester resin which will produce composite particle board. This study aims to determine the physical characteristics of wood powder composite particle board polyester resin matrix with variations in mass fraction. The tests carried out are the bending test (ASTM D790-03), the impact test (ASTM E23- 16), the water absorption test (D570-98), and the SEM test. The highest bending strength test results for the composite particle board of teak wood powder with polyester resin matrix occurred at a mass fraction of 5%: 95% with a value of 67,948 MPa and the lowest was 24,929 MPa at a mass fraction of 15%: 85%. The highest bending strain was at the mass fraction of 5%: 95% with a value of 0.016 and the highest modulus of elasticity occurred at the mass fraction of 5%: 95% with a value of 5,36 GPa. The results of the mass fraction 5%: 95% impact test have the highest impact strength with a value of 0,0013 Nm/mm2. The water absorption capacity of teak wood powder composite particle board with polyester resin matrix obtained the lowest absorption value at the mass fraction of 5%: 95% with a value of 5.83%. SEM test results show the bond between the amplifier and the matrix. Keyword : Teak Wood Powder, Particle Board, Bending Test, Impact Test, Water Absorption, Composite, Polyester